2005
DOI: 10.1007/11502760_11
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Random Sequences from Quasigroup String Transformations

Abstract: Abstract. The need of true random number generators for many purposes (ranging from applications in cryptography and stochastic simulation, to search heuristics and game playing) is increasing every day. Many sources of randomness possess the property of stationarity. However, while a biased die may be a good source of entropy, many applications require input in the form of unbiased bits, rather than biased ones. In this paper, we present a new technique for simulating fair coin flips using a biased, stationar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…-improving the existing and defining new kinds of pseudo random number (and sequence) generators [11]; -defining primitives for hash functions [8], [9]; -defining primitives for stream cipher [7]; -design of random codes [10]; and many others.…”
Section: Resultsmentioning
confidence: 99%
“…-improving the existing and defining new kinds of pseudo random number (and sequence) generators [11]; -defining primitives for hash functions [8], [9]; -defining primitives for stream cipher [7]; -design of random codes [10]; and many others.…”
Section: Resultsmentioning
confidence: 99%
“…In the first RO -one latch, in the second RO -two latches, and in the N th -N latches. Output bits from the combined TRNG may still be biased and correlated for small N [8], [9]. To overcome this problem it seems to be necessary to use post-processing [10].…”
Section: Trng With Sha-256 Hash Functionmentioning
confidence: 98%
“…Keedwell [Dénes & Keedwell, 1992, Keedwell 1999 proclaimed the start of new era in cryptography by using the non-associative algebraic structures such as quasigroups and neofields. Since then there have been some attempts of designing quasigroup based pseudorandom number generators/cryptographic schemes [Kościelny, 1996, Kościelny & Mullen, 1999, Golomb et al 2001, Gligoroski, 2004, Gligoroski, 2005, Markovski et al, 2005, Satti and Kak, 2009, Battey and Parakh, 2013 but weaknesses have been found in them [Dichtl & Böffgen, 2012] and have seen relatively less success than chaos based systems. Some of the comprehensive and in-depth overviews of the recent developments and current state of the art in the field of applications of quasigrous in cryptology can be seen in [Shcherbacov, 2012, Mileva, 2014.…”
Section: Page4mentioning
confidence: 99%